PENSION SECURITY IN UKRAINE IN THE CONTEXT OF COMPLIANCE WITH MINIMUM INTERNATIONAL STANDARDS - KRUPA, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The full-scale military aggression against our country, causing a number of destructive socio-economic processes, at the same time intensified the European integration aspirations of Ukraine, which, first of all, requires bringing the principles of the functioning of state systems into compliance, at least, with the minimum standards adopted in the European Union. In this context, the issues of improving individuals social protection and, in particular, pension security as one of its key components, in terms of bringing pension payments into line with internationally recognized minimum, are gaining special relevance. The purpose of the study consists in comparative analysis of pension security levels in Ukraine and OECD countries with assessment of their minimum social security standards compliance. In the article highlighted the social security minimum standards, which must be observed by Ukraine as a signatory of the same name international Convention. Carried out a comparative analysis of the actual amounts of pension payments by types in Ukraine with their estimated values in the context of international minimum standards compliance. Was made a comparison of the average level of retirement age people’ income in individual OECD countries and in Ukraine. Studied the structure of pension recipients in Ukraine according to their income level. The current system of pension provision in Ukraine does not make it possible to ensure compliance with the minimum international social standards in terms of the values of the replacement coefficient for the amounts of pension payments. Thus, about 40% of pensioners in Ukraine are below the poverty line, as the amount of pensions they receive does not even reach the amount of the subsistence minimum per person established by the state. The specified situation becomes especially acute during the period of martial law and active hostilities in part of the territories of our state, which are accompanied by the loss of individuals not only of additional means of livelihood, but also of housing and property acquired during life. Therefore, in further studies of the identified problems, attention should be focused on finding ways to solve the existing problems of the pension system, optimized according to the criteria of the level of budget burden and the speed of implementation.